The Metabolic and Non-Metabolic Roles of UCK2 in Tumor Progression - Fu, Yi; Wei, Xin-dong; Guo, Luoting; Wu, Kai; Le, Jiamei; Ma, Yujie; Kong, Xiaoni; Tong, Ying; Wu, Hailong (Frontiers in Oncology, 2022)
Enhanced nucleoside metabolism is one of the hallmarks of cancer. UCK2 is a rate-limiting enzyme of the pyrimidine salvage synthesis pathway to phosphorylate uridine and cytidine to uridine monophosphate (UMP) and cytidine monophosphate (CMP) respectively. Recent studies have shown that UCK2 is over-expressed in many types of solid and hematopoietic cancers, closely associates with poor prognosis, and promotes cell proliferation and migration in lung cancer and HCCs. Although UCK2 is thought to catalyze sufficient nucleotide building blocks to support the rapid proliferation of tumor cells, we and other groups have recently demonstrated that UCK2 may play a tumor-promoting role in a catalytic independent manner by activating oncogenic signaling pathways, such as STAT3 and EGFR-AKT. By harnessing the catalytic activity of UCK2, several cytotoxic ribonucleoside analogs, such as TAS-106 and RX-3117, have been developed for UCK2-mediated cancer chemotherapy. Moreover, we have demonstrated that the concurrent targeting of the catalytic dependent and independent features of UCK2 could synergistically inhibit tumor growth. These findings suggest that UCK2 may serve as a potential therapeutic target for cancer treatment. In this mini-review, we introduced the genomic localization and protein structure of UCK2, described the role of UCK2 in tumor development, discussed the application of UCK2 in anti-tumor treatment and proposed concurrent targeting of the catalytic and non-catalytic roles of UCK2 as a potential therapeutic strategy for cancer treatment.